Vinylation of Benzylic Amines via C–N Bond Functionalization of Benzylic Pyridinium Salts - Guan, Weiye; Liao, Jennie; Watson, Mary P. (Synthesis, 2018)
Cross-couplings of benzylic pyridinium salts and vinylboronic acids or esters have been developed. Via benzylic pyridinium intermediates, benzylic amines can be engaged in these cross-couplings through C–N bond functionalization. This method boasts mild reaction conditions and excellent tolerance for heteroaryl substituents and a range of functional groups.
Keywords: allyl complexes; amines; benzylation; catalysis; cross-coupling; nickel